Microtube Array Membrane (MTAM)-Based Encapsulated Cell Therapy for Cancer Treatment - Chee Ho Chew; Chih-Wei Lee; Wan-Ting Huang; Li-Wei Cheng; Amanda Chen; Tsai-Mu Cheng; Yen-Lin Liu; Chien-Chung Chen (Membranes, 2020)
The treatment of cancer has evolved significantly in recent years with a strong focus on immunotherapy. Encapsulated Cell Therapy (ECT) for immunotherapy-based anti-cancer treatment is a unique niche within this landscape, where molecules such as signaling factors and antibodies produced from cells are encapsulated within a vehicle, with a host amount of benefits in terms of treatment efficacy and reduced side effects. However, traditional ECTs generally lie in two extremes; either a macro scale vehicle is utilized, resulting in a retrievable system but with limited diffusion and surface area, or a micro scale vehicle is utilized, resulting in a system that has excellent diffusion and surface area but is unretrievable in the event of side effects occurring, which greatly compromises the biosafety of patients. In this study we adapted our patented and novel electrospun Polysulfone (PSF) Microtube Array Membranes (MTAMs) as a ‘middle’ approach to the above dilemma, which possess excellent diffusion and surface area while being retrievable. Hybridoma cells were encapsulated within the PSF MTAMs, where they produced CEACAM6 antibodies to be used in the suppression of cancer cell line A549, MDA-MB-468 and PC 3 (control). In vitro and in vivo studies revealed excellent cell viability of hybridoma cells with continuous secretion of CEACAM6 antibodies which suppressed the MDA-MB-468 throughout the entire 21 days of experiment. Such outcome suggested that the PSF MTAMs were not only an excellent three-dimensional (3D) cell culture substrate but potentially also an excellent vehicle for the application in ECT systems. Future research needs to include a long term in vivo >6 months study before it can be used in clinical applications.